Time Extension Issues of Public Procurement Contracts at Conflict-Effected Contexts - Bhatta, Jayendra Prasad; Sain, Manoj (A Bi-annual South Asian Journal of Research & Innovation, 2024)
Most of the public procurement and contract management (PCM) operations particularly in developing countries including the countries affected by the conflict encounter delay problems leading to time extension which creates a lot of controversies, disputes and produce significant impacts on project performance. However, there are very few researches have been conducted in the conflict-affected environment specifically to examine context based key factors those adversely effects the completion of the public procurement contract within the allocated time period. The aim of this research to explore possible key factors responsible for extension of time which affects the performance of infrastructure projects at conflict-affected contexts and evaluate their resolution practices. Mixed method approach of qualitative and quantitative techniques was adopted for this research work for which case studies of selected health infrastructure projects at conflict-affected situation was conducted. As part of methodological approach for this research, a systematic literature review (SLR), content analysis (CA) of project documents, in-depth interviews and questionnaires survey involving project managers, contractors, suppliers, consultants and facility owners was adopted. Among the several conflict-affected countries in the world, Timor-Leste located in East-Asia was selected on the basis of purposive selection procedure for this research study. A list of key factors that cause time overrun at conflict-affected situation is prepared based on the findings of SLR and content analysis of the project documents. From the selected 10 project sites (cases) at central, regional and referral level, 50 candidates have participated in the questionnaire survey and interviews including project managers and construction in-charges. Research findings include 23 factors those caused the issues of time-extension of the projects and listed their resolution procedures adopted during project execution process at conflict-effected situations. Findings of this research work will contribute for better understanding of time extension issues and their resolution methods for successful execution of PCM operations at conflict effected situations.